Some Sunny Day : My Autobiography - Lynn, Vera (London HarperCollins, 2009)
"Born Vera Welch in 1917, Dame Vera Lynn's career began at just seven years old when she sang professionally in East End Working Men's Clubs. A successful radio career with Joe Loss and Charlie Kunz in the 1920s and '30s followed - but it was with World War II that she became famous." "With her radio show 'Sincerely Yours', Vera connected emotionally with the men fighting for their country and those left behind praying for their loved ones, and became known as 'The Forces' Sweeheart'. Performing the songs that she will always be associated with - 'We'll Meet Again' and 'The White Cliffs of Dover' among others - Vera toured Egypt, India and Burma with the Entertainment National Services Association, bringing troops a sense of 'back home'. But what she saw out there affected her profoundly." "Her career after the war flourished, but Vera never left behind her wartime role. Still heavily involved with veteran and other charities, this is Dame Vera's story of her life and her war - from bombs and rations to broadcast and air raids, and the searing heat of her appearances abroad."
Include Color Illustration and Index
Keywords: Women singers -- Singers -- World War (1939-1945)